2020
DOI: 10.3390/en13081967
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Parameters Determining the Optimal Properties of Coal as a Natural Sorbent

Abstract: Selection of the optimal properties of coal as a natural sorbent, both as a sample collected from a seam or of the coal seam itself, requires various parameters to be determined and may not be based on the knowledge of metamorphism degree only. In order to improve the predictions of sorption capacity and the kinetics, analyses of correlation and multiple regression based on the results of laboratory studies were performed for 15 coal samples with various coal rank. The maximum vitrinite reflectance (R0) for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…there is a notable difference in their microhardness [ 28 ]. Studies conducted in recent years (own and of other researchers) proves that the results of coal microhardness parameter analysis with the changing degree of coalification may be somewhat different than the previous literature data (data from [ 30 ]). However, all study results, both those included in the archival studies and the current ones, presented recently by the authors of this publication show that microhardness properties may be an sign of specific coal behaviour and indicate features responsible for increased coal outburst susceptibility.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…there is a notable difference in their microhardness [ 28 ]. Studies conducted in recent years (own and of other researchers) proves that the results of coal microhardness parameter analysis with the changing degree of coalification may be somewhat different than the previous literature data (data from [ 30 ]). However, all study results, both those included in the archival studies and the current ones, presented recently by the authors of this publication show that microhardness properties may be an sign of specific coal behaviour and indicate features responsible for increased coal outburst susceptibility.…”
Section: Discussionmentioning
confidence: 74%
“…The basic characteristics of coals were obtained via technical analysis, which determined the total moisture content W t , volatile content V daf and ash content A d in the coal [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hou et al [21] determined that the hardness and elastic modulus are in the order of exinite < vitrinite < inertinite by employing depth-sensing nanoindentation. Kožušníková [22] revealed that the Vickers microhardness and elastic modulus of coal sample with higher coalification were lower than of coal sample with lower coalification and also, Godyńand et al [23] found that micro-hardness value decreases with metamorphism degree using Vickers hardness test in Silesian Coal Basin, Poland. Fender et al [24] suggested that thermally immature liptinite macerals have a lower modal modulus than the inertinites and the modal Young's modulus of all macerals increases with maturity, based on atomic force microscopy.…”
Section: Introductionmentioning
confidence: 99%